Descriptions of the mature larva and adult female of Pseudopyrochroa girardi Young from Southwest China (Coleoptera: Pyrochroidae: Pyrochroinae), with natural history observations - Zhan, Zhihong; Jing, Kaixiang; Young, Daniel K. (Zootaxa, 2023)
Larvae of Pseudopyrochroa girardi were collected beneath bark and in coarse, decaying woody debris of dead logs in Ya’an City, Sichuan Province, China. The species association was confirmed by rearing both males and females to the adult stage. The last instar larva is described and illustrated, along with the first description of the adult female. Observations relating to the larval/pupal macro- and microhabitats and natural history are also provided and illustrated. A brief discussion of the significance of such discoveries is presented in relation to the “Mountains of Southwest China” global biodiversity hotspot and conservation implications relating to forests and saproxylic species like Pyrochroidaae.